2010
DOI: 10.3766/jaaa.21.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Electrocochleography: A Review of Recording Approaches, Clinical Applications, and New Findings in Adults and Children

Abstract: Research related to expanding and improving the clinical use of electrocochleography (ECochG) has been ongoing for 25 yr at the University of Kansas Medical Center. This article presents highlights of findings from our laboratory during this period that have contributed to current ECochG recording approaches and clinical applications. A review of new data related to improving the sensitivity of ECochG in the diagnosis of Ménière's disease, the use of an ear canal recording approach for improving auditory brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 36 publications
2
55
0
Order By: Relevance
“…16 While ECOG is a clinically accepted routine, it is often poorly interpreted in a Meniere's population, where there is a significant hearing loss. 1,13,26,28 In general, ECOG sensitivity does not seem to be more than 67%. 7 A better measure for the vestibular state would directly measure the dynamic response of the vestibular system to both excitatory and inhibitory inputs, and derive a measure of its dynamic range.…”
Section: Introductionmentioning
confidence: 89%
“…16 While ECOG is a clinically accepted routine, it is often poorly interpreted in a Meniere's population, where there is a significant hearing loss. 1,13,26,28 In general, ECOG sensitivity does not seem to be more than 67%. 7 A better measure for the vestibular state would directly measure the dynamic response of the vestibular system to both excitatory and inhibitory inputs, and derive a measure of its dynamic range.…”
Section: Introductionmentioning
confidence: 89%
“…The electrode setup and the recording parameters that we used in this study were based upon the study reported by Ferraro [16] . The ground electrode was placed on the forehead (Fz), the active electrode was placed on the eardrum, and the reference electrode was placed on the contralateral mastoid.…”
Section: Stimulus and Recording Parametersmentioning
confidence: 99%
“…The SP/AP amplitude ratio and SP/AP area ratio were based on Ferraro [16] . The SP and the AP amplitudes were measured from the waveform peak and compared to the pre-stimulus baseline (Figure 1).…”
Section: Sp/ap Amplitude Ratio and Sp/ap Area Ratio Calculationmentioning
confidence: 99%
“…Electromagnetic interference can be a major problem in CMW measurements as it can contaminate CMW measurements and can be difficult to avoid. However, the use of appropriate shielding may prevent CMW responses from being contaminated (Ferraro 2010). A low signal to noise ratio is another great challenge for CMWs measured at the concha.…”
Section: Limitations For the Use Of Cmwsmentioning
confidence: 99%
“…However, it is difficult to measure cochlear microphonics (CMs) by using narrowband frequencies in most clinics, because the conventional approach uses broadband frequencies such as a click in the electrocochleogram (ECoG) (Ferraro 2010). The click is much more transient in time and much broader in frequency than the stimulus used in tone burst ABRs and DPOAEs (Zhang & Abbas 1997).…”
Section: Introductionmentioning
confidence: 99%